Preservative leaching from chromated copper arsenate (CCA) treated timber to the soil enviroment - Chin, Willy Siaw Min (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Wood has been used for centuries as building materials and the concern of le~ching of toxic elements into the soils and groundwater arise when Chromated Copper Arsenate (CCA) wood preservatives were used to extend the service life of timbers in soil contact against decay and termites infestation. In this study, the levels of total copper, chromium and arsenic within CCAtreated poles and in soils surrounding the poles in service at a plot in Timber Research and Technical Training Centre, Kuching, Sarawak, Malaysia since 1980 or 1981, were investigated There are significant decreases of CCA salt retention in poles after 30 years of weathering (p<0.05) but with insignificant differences (p>0.05) between retention of CCA salt in wood 1300 mm above ground level and 0-20 mm below ground level. The levels of these elements were found to be significantly elevated compared to control sites (background level) in soils immediately adjacent to the treated poles. The metal levels were highest at the soil surface in contact with the poles but decreased with distance and depth. Mean extractable arsenic levels ranged from 14.53 up to 100.06 mg/kg, chromium levels from 23.31 to 148.32 mg/kg and mean copper levels from 21.83 to 104.72 mg/kg. The results show that the soil is contaminated, albeit slightly, after 30 years exposure of CCA treated wood in ground contact.